2022
DOI: 10.7554/elife.71624
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic rejuvenation of human cells by maturation phase transient reprogramming

Abstract: Ageing is the gradual decline in organismal fitness that occurs over time leading to tissue dysfunction and disease. At the cellular level, ageing is associated with reduced function, altered gene expression and a perturbed epigenome. Somatic cell reprogramming, the process of converting somatic cells to induced pluripotent stem cells (iPSCs), can reverse these age-associated changes. However, during iPSC reprogramming, somatic cell identity is lost, and can be difficult to reacquire as re-differentiated iPSCs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(111 citation statements)
references
References 68 publications
(130 reference statements)
3
105
0
3
Order By: Relevance
“…Epigenetic clocks such as the pan-tissue clock for humans 4 indicate that cellular reprogramming based on the Yamanaka factors (OSKM) leads to age reversal 4,26 . To assess whether the universal clocks exhibit the same age reversal pattern during reprogramming, we applied Clock 2 and Clock 3 to a previously published reprogramming dataset in human dermal fibroblasts (HDFs) (Ohnuki et al, 2014).…”
Section: Oskm-based Reprogrammingmentioning
confidence: 99%
“…Epigenetic clocks such as the pan-tissue clock for humans 4 indicate that cellular reprogramming based on the Yamanaka factors (OSKM) leads to age reversal 4,26 . To assess whether the universal clocks exhibit the same age reversal pattern during reprogramming, we applied Clock 2 and Clock 3 to a previously published reprogramming dataset in human dermal fibroblasts (HDFs) (Ohnuki et al, 2014).…”
Section: Oskm-based Reprogrammingmentioning
confidence: 99%
“…They also reported that some of these changes could be reversed [88] interpreting "aging as a disease", a notion that has already been proposed in ancient times [89] and has recently garnered attention [89,90]. Regardless of whether aging should be seen as a disease or not, extending not only the lifespan but also the health span [1,89,90] and possibly even rejuvenation [27] are of great interest. In this study, we analyzed a publicly available RNA Seq dataset using bioinformatic tools.…”
Section: Discussionmentioning
confidence: 99%
“…The dataset contains RNA-Seq data of dermal fibroblasts donated by ten progeria patients and 133 "apparently healthy" individuals (aged 1 to 96 years according to their metadata) [16,17]. Their dataset is publicly available on the Gene Expression Omnibus (GEO) database [18] under accession number GSE113957 [16,17] Since its publication in November 2018, the article by Fleischer et al has been cited 37 times in PubMed (until May 2022), with 13 of the citing papers mentioning the use of the GSE113957 dataset from the Fleischer et al paper [19][20][21][22][23][24][25][26][27][28][29][30][31] (as described in Table 1). According to the publications in PubMed, the dataset alone contributed to 8 studies investigating aging [20,[22][23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…In a separate cohort of patients with severe obesity, a decrease in epigenetic ∆age was observed 12 months after bariatric surgery (Fraszczyk et al, 2020). human dermal fibroblasts (Gill et al, 2022).…”
Section: Interventions That Turn Back Aging Clocks In Humansmentioning
confidence: 98%
“…A final point of consideration is the reversal of an aging clock, which has been reported in vivo in mice (Browder et al, 2022;Y. Lu et al, 2020) and in vitro in human cells (Gill et al, 2022) in response to reprogramming. As shown in Table 1, epigenetic age can also be reversed in response to different interventions.…”
Section: Outstanding Questions and Limitations In The Fieldmentioning
confidence: 99%